# Area of Ellipse/Proof 1

## Theorem

Let $K$ be an ellipse whose major axis is of length $2 a$ and whose minor axis is of length $2 b$.

The area $\mathcal A$ of $K$ is given by:

$\mathcal A = \pi a b$

## Proof

Let $K$ be an ellipse aligned in a cartesian coordinate plane in reduced form.

Then from Equation of Ellipse in Reduced Form:

$\dfrac {x^2} {a^2} + \dfrac {y^2} {b^2} = 1$

Thus:

$y = \pm b \sqrt {1 - \dfrac {x^2} {a^2} }$
 $\displaystyle \mathcal A$ $=$ $\displaystyle b \int_{-a}^a \paren {\sqrt {1 - \dfrac {x^2} {a^2} } - \paren {-\sqrt{1 - \dfrac {x^2} {a^2} } } } \rd x$ $\displaystyle$ $=$ $\displaystyle b \int_{-a}^a 2 \sqrt {1 - \dfrac {x^2} {a^2} } \rd x$

Let $x = a \sin \theta$ (note that we can do this because $-a \le x \le a$).

Thus:

$\theta = \arcsin \paren {\dfrac x a}$

and:

$\d x = a \cos \theta \rd \theta$

Then:

 $\displaystyle \mathcal A$ $=$ $\displaystyle b \int_{\arcsin \paren {\frac {-a} a} }^{\arcsin \paren {\frac a a} } 2 a \sqrt {1 - \frac {\paren {a \sin \theta}^2} {a^2} } \cos \theta \rd \theta$ Integration by Substitution $\displaystyle$ $=$ $\displaystyle b \int_{-\frac {\pi} 2}^{\frac {\pi} 2} 2 a \sqrt {1 - \sin^2 \theta} \cos \theta \rd \theta$ $\displaystyle$ $=$ $\displaystyle b \int_{-\frac {\pi} 2}^{\frac {\pi} 2} 2 a \sqrt {\cos^2 \theta} \cos \theta \rd \theta$ Sum of Squares of Sine and Cosine $\displaystyle$ $=$ $\displaystyle a b \int_{-\frac {\pi} 2}^{\frac {\pi} 2} 2 \cos^2\theta \rd \theta$ $\displaystyle$ $=$ $\displaystyle a b \int_{-\frac {\pi} 2}^{\frac {\pi} 2} \paren {1 + \cos \paren {2 \theta} } \rd \theta$ Double Angle Formula for Cosine: Corollary 1 $\displaystyle$ $=$ $\displaystyle a b \sqbrk {\theta + \frac 1 2 \sin \paren {2 \theta} }_{-\frac {\pi} 2}^{\frac {\pi} 2}$ Integration of Constant and Primitive of Cosine Function $\displaystyle$ $=$ $\displaystyle a b \paren {\frac {\pi} 2 + \frac 1 2 \sin \paren {2 \cdot \frac {-\pi} 2} - \frac {-\pi} 2 - \frac 1 2 \sin \paren {2 \cdot \frac {\pi} 2} }$ $\displaystyle$ $=$ $\displaystyle a b \paren {2 \cdot \frac {\pi} 2 + 2 \cdot \frac 1 2 \cdot 0}$ $\displaystyle$ $=$ $\displaystyle \pi a b$

$\blacksquare$